1991
DOI: 10.1002/ptr.2650050610
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of Cedronella canariensis (L.) var. Canariensis extracts for antiinflammatory and analgesic activity in rats and mice

Abstract: Several extracts and fractions from Cedronella canuriensk (L.) have been submitted to analgesic, antipyretic and antiinflammatory tests on rats and mice. The experimental results obtained justified the utilization of this species as an anticatarrh and antiinfluenza agent in Canarian folk medicine. Its acute toxicity turned out to be low as measured in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Only limited information is available on the chemical composition of Ceclronella (7)(8)(9). First results on the oil from both "varieties"were published by Engel et al (10,ll) followed by L6pez-Garcia et al (12) and Lawrence ( 1 3~4 ) .…”
mentioning
confidence: 96%
“…Only limited information is available on the chemical composition of Ceclronella (7)(8)(9). First results on the oil from both "varieties"were published by Engel et al (10,ll) followed by L6pez-Garcia et al (12) and Lawrence ( 1 3~4 ) .…”
mentioning
confidence: 96%
“…Infusion de feuilles utilisée comme calmant, hypnotique et tonique ; Sambucus lanceolata (sabugueiro) (Madeira elder) (Caprifoliaceae) (Fig. 2) [12], béta-pinène (de 19,6-20 % dans l'huile de feuilles à 32 % dans l'huile de fleurs), et encore béta-myrcène (9,3 %), sabinène, myrtényl méthyl éther (2,9 %), béta-caryophyllène, myrténol, béta-phellandrène et limonène. Dans la sous-espèce anisata, 257 composants ont été isolés, le constituant principal étant le methylchavicol (82,2 %), béta-pinène (10,2 %), 13-caryophyllène (2,8 %), pinocarvone (0,9 %), etc.…”
Section: La Flore Médicinale De Madèreunclassified
“…The antiinflammatory effects of the plant extracts may be related to their constituents. Thus, the acetone extract contains triterpenes as well as p-sitosterol (Hernandez-Perez et al, 1994), and some of these have been shown to possess antiinflammatory activity (Chaturvedi ef al., 1976;Lopez-Garcia et al, 1991). The methanol extract and syrup, on the other hand, contain tannins (Hernandez-Perez et al, 1994), and some of them have been shown to exert antiinflammatory activity through the inhibition of synthesis of 5lipoxygenase, an inflammatory mediator (Kimura er al., 1987).…”
Section: Antipyretic Studymentioning
confidence: 99%